Penerapan Bahan Ajar Berbasis Web Di MTSN 2 Bengkulu Tengah - Hermawansa; Yul , Fadlul Amdhi; Susanto , Edy; Nurhanifah (Universitas Dehasen Bengkulu, 2022)
Community Service through Training on the Preparation of Web-Based Teaching Materials for Teachers of MTsN 2 Bengkulu Tengah. The target of this training is MTsN 2 Bengkulu Tengah Teachers. The purpose of carrying out this activity is to train teachers at MTsN 2 Bengkulu Tengah in compiling web-based teaching materials. The method used includes a brief presentation of learning model material, Web-based E-Learning material, then followed by discussion, question and answer, and giving independent assignments to each participant. The results of the service carried out showed that the Web-Based e-Learning Model Interactive Teaching Materials fulfilled the eligibility with a description for displaying web media teaching materials included in the Good category (with an average percentage of 78.39%), for teaching materials included in the Good category (with the average percentage is 88.47%), and for students' perceptions of teaching materials it is in the Fairly Good category (with an average percentage of 66.84%). The results of this dedication can be used as a basis for policy making for the Central Bengkulu Regency Education and Culture Office to try to apply the innovative learning model and learning tools for the Web-based E-learning model in other schools in Central Bengkulu Regency.